Tackling the unyielding: testing two novel approaches against NDM-producing Enterobacterales and Pseudomonas aeruginosa isolates collected in India - Yamuna Devi Bakthavatchalam; Bijayini Behera; Anand Shah; Purva Mathur; Raja Ray; Bashir Ahmed Fomda; Kamini Walia; Balaji Veeraraghavan (Microbiology Spectrum)
ABSTRACT The in vitro activity of two novel antibiotics with different modes of action, (i) siderophore cefiderocol and (ii) β-lactam-enhancer mechanism-based cefepime/zidebactam, was tested against New Delhi Metallo-β-lactamase (NDM)-producing Enterobacterales and Pseudomonas aeruginosa collected in India. Minimum inhibitory concentrations of antibiotics against multicentric NDM-producing Escherichia coli (n = 117), Klebsiella pneumoniae (n = 103), and P. aeruginosa (n = 72) were determined by the reference broth microdilution method. Among E. coli, 111 isolates were NDM-alone, and six were NDM + OXA-48-like producers. Among K. pneumoniae, 47 and 56 isolates were NDM-alone and NDM + OXA-48-like producers, respectively. All E. coli isolates harbored four amino acid inserts in their penicillin-binding protein 3. Using the highest susceptible breakpoint among CLSI, FDA, and EUCAST interpretive criteria, cefiderocol susceptibility was 39.3%, ≤80%, and 57%, for NDM ± OXA-48-like-producing E. coli, NDM ± OXA-48-like-producing K. pneumoniae, and NDM-producing P. aeruginosa, respectively. At a cefepime break point of ≤8 mg/L, 100% of Enterobacterales and ≥90% of P. aeruginosa isolates were cefepime/zidebactam-susceptible. NDM being a dominant carbapenemase among Enterobacterales and P. aeruginosa in India, the variable activity of cefiderocol against NDM producers is a concern. Post approval, cefepime/zidebactam could offer a promising treatment option against NDM producers.IMPORTANCEMetallo-β-lactamases are therapeutically challenging due to the limited treatment options. Against such isolates, currently approved newer β-lactam/β-lactamase inhibitor combinations are ineffective. In this study, we tested siderophore cephalosporin, cefiderocol, which utilizes an unconventional iron uptake pathway for efficient cellular penetration, and cefepime/zidebactam that utilizes novel β-lactam enhancer mechanisms for overcoming diverse carbapenemases. Cefiderocol showed limited activity against Escherichia coli isolates co-harboring New Delhi metallo-β-lactamase (NDM) with PBP3 insert, dual carbapenemase (NDM with OXA-48 like)-producing Klebsiella pneumoniae, and NDM-producing Pseudomonas aeruginosa isolates, while cefepime/zidebactam potently inhibited NDM-producing Enterobacterales and P. aeruginosa isolates. NDM being a dominant carbapenemase among Enterobacterales and P. aeruginosa in India, the variable activity of cefiderocol against NDM producers is a concern. Post approval, cefepime/zidebactam could offer a promising treatment option against NDM producers.